ENGLISH COMPETENCE NEEDED BY NURSING STUDENTS AT BAITURRAHIM VOCATIONAL HIGH SCHOOL JAMBI - Warahmah, Mawaddah; Junaidi, Adi Saputra; Sari, Indah Permata (JR-ELT (Journal of Research in English Language Teaching), 2022)
The research aimed at finding out the English competence needed by nursing department students during the course of their studies as well as in preparing themselves for their future work as nurses at the international level. The competence needed by the students and nurses-to-be was then used as the basis for designing the English material to be proposed to and adopted by the curriculum at Baiturrahim Vocational high School Jambi. This research took place at the Baiturrahim Vocational high School Jambi. The research was descriptive qualitative in nature. This study used interviews and observations to collect the data to answer the research questions. The source of data was sixteen nursing students, one teacher and the headmaster. The results of the data analysis indicated that there were ten main competencies to acquire by nursing students to function properly in the nursing profession. The competencies included giving explanation of the escort of basic treatment, giving the health counseling, giving the explanation of the escort of pathology and its treatment, translating the data collection, medical record and report data, executing the basic treatment, using communication skills in a healthcare, approaching to the patient, listening, questioning and diagnosing, giving explanation and advice, and communicating in term of involving patient in management. The ten basic competencies were then used as the bases in designing the syllabus for the Nursing Department students. The type of syllabus chosen was competence-based one. The syllabus stated the competency standards, basic competencies along with their indicators, list of teaching materials, suggested learning experience, time allotment, list of resources and media, and assessment